Up-Regulation of p53/miR-628-3p Pathway, a Novel Mechanism of Shikonin on Inhibiting Proliferation and Inducing Apoptosis of A549 and PC-9 Non–Small Cell Lung Cancer Cell Lines - Jieli Pan (Frontiers Media S.A., 2021)
Shikonin (SHK) is a pleiotropic agent with remarkable cell growth inhibition activity against various cancer types, especially non–small cell lung cancer (NSCLC), but its molecular mechanism is still unclear. Our previous study found that miR-628-3p could inhibit the growth of A549 cells and induce its apoptosis. Bioinformatics analysis predicted that miR-628-3p promoter sequence contained p53 binding sites. Considering the regulatory effect of SHK on p53, we speculate that SHK may inhibit the growth and induce apoptosis of NSCLC cells by up-regulating miR-628-3p. CCK-8 and EdU assay confirmed the inhibitory effect of SHK on A549 and PC-9 cells. Meanwhile, quantitative reverse transcription–polymerase chain reaction and Western blot showed that SHK could promote the expression of p53 and miR-628-3p in a dose-dependent manner. Overexpression of p53 or miR-628-3p can inhibit the growth and promote apoptosis of A549 and PC-9 cells, while silencing p53 or miR-628-3p has the opposite effect. Dual luciferase reporting assay and ChIP (chromatin immunoprecipitation) assay further verified the direct interaction between p53 and the promoter of miR-628-3p. Gene knockdown for p53 or miR-628-3p confirmed that SHK inhibits the growth and induces apoptosis of A549 and PC-9 cells at least partly by up-regulating p53/miR-628-3p signaling pathway. Therefore, these novel findings provide an alternative approach to target p53/miR-628-3p axis and could be used for the development of new treatment strategies for NSCLC.